Odpowiedzi

2010-03-04T20:45:45+01:00
A)5*[0,4-2\5:(-2)]=5*[0,4-(-2)]=5*(0,4+2)=5*2,4=12
b[0,8-(-1,2*5\12*0,8)]:(-1\8)=[0,8-(-0,4)]:(-1/8)=(0,8+0,4):(-1/8)=1,2:(-1/8)=-9,6
c)-100:{-[2i3\4-(-0,5):(-1i1\2)]}=-100:{-[2,75+0,5:(-1,5)]=-100:{-[2,75+(-⅓)]}=
=-100:{-[2 i 5/12]}=-100:(-2 i 5/12)=1200/29=41,38
2010-03-04T22:13:30+01:00
Rozwiąż:
a)5*[0,4-2\5:(-2)]=5*[0,4+1\5]=5*[0,4+0,2]=5*[0,6]=3
b)[0,8-(-1,2*5\12*0,8)]:(-1\8)=[0,8-(-6\12*0,8)]:(-1\8)=
[0,8+0,4]:(-1\8)=1,2:(-1\8)=-9,6

c)-100:{-[2i3\4-(-0,5):(-1i1\2)]}=-100:{-[2,75-(-0,5):(-1,5)]}=
-100:{-[2 i 3/4-1/3]}=-100:{-[2 i 9/12-4/12]}=-100:{-[2 i 5/12]}=
-100:{-29/12}=-100*{-12/29}=1200/29